Flexural response of steel-fiber-reinforced concrete beams: Effects of strength, fiber content, and strain-rate. (November 2015) - Yoo, Doo-Yeol; Yoon, Young-Soo; Banthia, Nemkumar
Abstract: This study aims to investigate the flexural behavior of steel-fiber-reinforced concrete (SFRC) beams under quasi-static and impact loads. For this, a number of SFRC beams with three different compressive strengths ( f c ' of approximately 49, 90, and 180 MPa) and four different fiber volume contents ( vf of 0, 0.5, 1.0, and 2.0%) were fabricated and tested. The quasi-static tests were carried out according to ASTM standards, while the impact tests were performed using a drop-weight impact test machine for two different incident potential energies of 40 and 100 J. For the case of quasi-static load, enhancements in the flexural strength and deflection capacity were obtained by increasing the fiber content and strength, and higher toughness was observed with an increase in the fiber content. For the case of impact load, an increase in the load carrying capacity was obtained by increasing the potential energy and strength, and an improvement in the post-peak behavior was observed by increasing the fiber content. The increases in fiber content and strength also led to enhancements in residual flexural performance after impact damage. Finally, the flexural strength became less sensitive to the strain-rate (or stress-rate) as the strength of concrete increased.